Platelet Signaling in Primary Haemostasis and Arterial Thrombus Formation: Part 2 - Scharf, Rüdiger E. (Hämostaseologie, 2018)
Platelet signal transduction is the focus of this review. While ‘classic’ platelet signaling through G protein–coupled receptors in response to fluid-phase agonists has been extensively studied, signaling mechanisms linking platelet adhesion receptors such as GPIb-IX-V, GPVI and α2β1 to the activation of αIIbβ3 are less well established. Moreover, ‘non-haemostatic’ pathways can also activate platelets in various settings, including platelet–immune or platelet–tumour cell interactions, platelet responses to neutrophil extracellular traps, or stimulation by microbial pathogens. Genetically determined integrin variants can modulate platelet function and increase thrombogenicity. A typical example is the Pro33 (HPA-1b) variant of αIIbβ3. Recent advances in the genotype–phenotype relation of this prothrombotic variant and its impact on outside-in signaling will be reviewed.
Keywords: platelet signaling; integrin αIIbβ3; G protein–coupled receptors; calcium mobilization